The Effect of Net Profit Margin, Return on Asset, Return on Equity on Share Prices in The Southeast Asian Metal Industry - Sunaryo, Deni (International Journal of Science, Technology & Management, 2020)
This study aims to see the effect of Net Profit Margin, Return On Assets and Return On Equity. This study uses secondary data. The sample used is nine metal companies that are on the Southeast Asian Stock Exchange. The independent variables in this study are Net Profit Margin, Return On Assets and Return On Equity. Sampling in this study using purposive sampling technique. The data analysis method used is the classical assumption test, hypothesis test, F test and t test. Based on the research results, it is known that Net Profit Margin, Return On Assets and Return On Equity do not have a significant effect on stock prices. The results of the F test indicate that Net Profit Margin, Return On Asset and Return On Equity together do not have a significant effect on stock prices. Recommendations for further research should be able to convince investors by increasing the value of Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE). Because the higher the value of Net Profit Margin (NPM), Return On Asset (ROA), Return On Equity (ROE) and similar research is expected to increase the research sample or replace other variables related to stock prices and use a test tool other than multiple regression.